Using Self-Determination Theory to Explore Enjoyment of Educational Interactive Narrative Games: A Case Study of Academical - Grasse, Katelyn M.; Kreminski, Max; Wardrip-Fruin, Noah; Mateas, Michael; Melcer, Edward F. (Frontiers in Virtual Reality, 2022)
Choice-based interactive storytelling games such as Academical, our responsible conduct of research training game, show great promise as a novel way of providing efficacious ethics training. However, much work remains to determine what factors of such games contribute to their advantages over traditional text-based training tools, especially if we hope to further improve their enjoyment, engagement and efficacy. In this article, we present a case study exploring how the motivational factors of Self-Determination Theory (SDT) underlie players' perceived most and least enjoyable experiences arising from the design of Academical. Specifically, we discuss how certain elements of Academical's design influence different SDT factors and subsequently player experience, as well as how such elements can be changed to further improve the game. Furthermore, our work highlights potential limitations of existing conceptualizations for the relatedness factor of SDT---discussing ways that it can be extended to properly understand player enjoyment within single-player educational interactive narrative games.